Enhancing competitiveness and resilience of tourism in crises condition: Experiences from Eastern Partnership countries - Mihai Talmaciu; Irina Manolescu (CES Working Papers, 2021)
This paper discusses the major challenges for the present European Commission, starting with Brexit and ending with issues such as EU Eastern Enlargement from today's perspectives, trying to explain why it is difficult to talk about enlargement in a fragmented European Union. How will the European Neighborhood Policy and Enlargement Negotiations evolve in the actual mandate of the European Commission? Did the European Commission succeed in offering Eastern states the opportunity to join the European Union by developing instruments encouraging states to meet the accession criteria? A qualitative analysis will be used to highlight the novelty elements analyzed by the proposed theme; the author uses a study case using as research instruments discourse and content analysis. Therefore, the main objective of this research paper is to highlight how the European leaders' discourse on a possible enlargement of the European Union has evolved.The long-term goals set for the post-2020 EaP policy are oriented to support economic resilience. Due to its peculiarities, tourism has proved to be one of the most sensitive economic sectors to the manifestation of multiple crisis experiences. The present study aims to: study and identify the effects of crises on tourism competitiveness and performances in Eastern Partnership countries; to identify measures by which the European Union authorities intend to counteract the effects of crises and improve the response capacity of governments and tourism companies; and to identify actions through which the tourism industry can improve its capacity to manage the various crisis phenomena. To achieve these objectives, the authors used European Commission programmatic documents and reports, statistical reports, data and information on the effects of crises on the activity of the tourism industry in EAP countries. In the frame of the partnership and cooperation relations between the European Union and the EaP countries, special attention has been paid to the support measures established to counteract the negative effects of the pandemic crisis.
Keywords: 330; competitiveness; Eastern Partnership policy; tourism; resilience; crisis